Hearing loss in pediatric patients with congenital rubella syndrome - Muyassaroh Muyassaroh; Nisa Alifia Rahmi (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2022)
Congenital rubella syndrome (CRS) is caused by rubella infection in pregnant women. It was estimated 100.000 children with CRS, with 46% found in developing countries. The CRS consists of symptoms like sensorineural hearing loss (SNHL), congenital heart disease, cataract or congenital glaucoma, and other symptoms. Sensorineural hearing loss is the commonest symptoms compared with others. This study aimed to determine the hearing loss in CRS in Dr. Kariadi Central Hospital, Semarang, Central Java. This was a descriptive study using data from medical records from CRS pediatric patients who had BERA examination from January 2019 until December 2020. The CRS was characterized with one or more symptoms: SNHL, congenital cataract, congenital heart disease, and laboratory IgG and/or IgM Rubella (+). The SNHL was described from refer OAE result, tympanometry A, and BERA with hearing threshold ≥40 dB. Follow-up evaluation was performed with Google form questionnaire. There were 55 CRS cases with 70.9% had bilateral SNHL, mostly with very severe hearing loss. Normal hearing was found in 16 children (28.1%). From 30 children who were followed up, there were 20 children who had bilateral SNHL with 30% were moderate-severe degree and 70% profound. With further multidisciplinary management in children with CRS and parental support, 65% children used hearing aid and 40% had auditory-verbal therapy (AVT). Evaluation of the AVT showed progress in 30% children. In conclusion, SNHL is found in 70.9% children with CRS. Further management using hearing aid and AVT shows progress on few children.